1994
DOI: 10.1346/ccmn.1994.0420502
|View full text |Cite
|
Sign up to set email alerts
|

The Al Pillaring of Clays. Part II. Pillaring with [Al13O4(OH)24(H2O)12]7+

Abstract: Abstract--Hectorite and saponite are exchanged with [AlI304(OH)24(H20)12] 7+ and the amount of Al 3+ adsorbed and Na § released are followed as a function of the exchange conditions. On saponite the reaction is a pure ion exchange with 2-2.15 mmol A13+/g adsorbed and release of 0.80 mmol Na+/g. On hectorite the ion exchange is accompanied by supplementary hydrolysis-polymerization of All3. When excess A1 is offered in the form of Al13, ion exchange is incomplete and is accompanied by precipitation and polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…A certain amount of a polyethylene oxide (PEO) surfactants of small molecular weights, with a general chemical formula CI 2 .1 4 H25-29 0(CH 2 CH 2 0)oH (n = [5][6][7][8][9][10][11][12], was added into the laponite dispersion which then became opaque. The suspension was stirred for 2 hours to allow sufficient mixing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A certain amount of a polyethylene oxide (PEO) surfactants of small molecular weights, with a general chemical formula CI 2 .1 4 H25-29 0(CH 2 CH 2 0)oH (n = [5][6][7][8][9][10][11][12], was added into the laponite dispersion which then became opaque. The suspension was stirred for 2 hours to allow sufficient mixing.…”
Section: Methodsmentioning
confidence: 99%
“…The development of pillared layered clays has provided very useful knowledge on the precursor solutions [ 1]. The structures of various oligomers in precursor solutions have been comprehensively studied [6,7]. In many eases, the pillaring solutions for the synthesis of pillared layered clays can be used for the synthesis of nanoconiposites.…”
Section: Introductionmentioning
confidence: 99%
“…Dilution and refluxing of the aluminum chlorhydrol (ACH) solution affects the concentration of the Keggin species in the pillaring solution (Bottero et al, 1982). Nonetheless, in PILC, the Keggin ion may not be the sole ion in the phyllosilicate interlayer (Schoonheydt et al, 1994). Upon beating, Keggin ions may undergo condensation reactions in the interlayer with the formation of higher polymers such as the A124-polycation (Fu et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent structure investigations of clay minerals intercalated with A1-OH polymers focused on the nature of the intercalating agent (Plee et al 1987;Hsu 1992;Schoonheydt et al 1993Schoonheydt et al , 1994Dubbin et al 1994). The 2VA1 nuclear magnetic resonance (NMR) spectra of the intercalating solutions normally show the presence of 2 species: octahedral A1 and tetrahedral AI, included in All3 oligomer-Keggin cation (Figueras et al 1990;Hsu 1992;Schoonheydt et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The 2VA1 nuclear magnetic resonance (NMR) spectra of the intercalating solutions normally show the presence of 2 species: octahedral A1 and tetrahedral AI, included in All3 oligomer-Keggin cation (Figueras et al 1990;Hsu 1992;Schoonheydt et al 1994). Although the Keggin cation has been a widely accepted intercalating species, Schoonheydt and Leehman (1992) and Hsu (1992) showed that intercalation is also possible with concentrated A1-OH solutions in which the Keggin cation is almost totaly absent.…”
Section: Introductionmentioning
confidence: 99%